2014
DOI: 10.1111/cge.12405
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐test genetic counseling services for hereditary breast and ovarian cancer delivered by non‐genetics professionals in the state of Florida

Abstract: Genetic counseling and testing for hereditary breast and ovarian cancer now includes practitioners from multiple healthcare professions, specialties, and settings. This study examined whether non-genetics professionals (NGPs), perform guideline-based patient intake and informed consent before genetic testing. NGPs offering BRCA testing services in Florida (n = 386) were surveyed about clinical practices. Among 81 respondents (response rate = 22%), approximately half reported: sometimes scheduling a separate se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 25 publications
(32 reference statements)
1
48
0
Order By: Relevance
“…These results may be contrasted with findings from our 2012 survey of 81 non-GHPs in which the majority of providers reported GC sessions of 30 minutes or less with many reporting limited or no discussion of recommended pre-test elements. 24 Thus, our recent provider level data is consistent with findings from the current study where over 40% of participants tested by non GHPs did not recall having had pre-test GC. However, our data also suggest that many non GHPs are performing pre-test counseling that includes discussion of many nationally recommended GC elements.…”
Section: Discussionsupporting
confidence: 90%
“…These results may be contrasted with findings from our 2012 survey of 81 non-GHPs in which the majority of providers reported GC sessions of 30 minutes or less with many reporting limited or no discussion of recommended pre-test elements. 24 Thus, our recent provider level data is consistent with findings from the current study where over 40% of participants tested by non GHPs did not recall having had pre-test GC. However, our data also suggest that many non GHPs are performing pre-test counseling that includes discussion of many nationally recommended GC elements.…”
Section: Discussionsupporting
confidence: 90%
“…17, 76 The small number of women who obtained genetic testing limits our ability to draw meaningful conclusions about the noninferiority of telephone counseling for risk management outcomes. Because our sample was from a single state, was largely non-Hispanic white, and had a personal history of cancer, our study may have limited generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…31,33,34,39,41,45,52,54,57 Of these, four studies provided descriptive information about PCPs' experiences discussing genetic risk and testing (2 relying on surveys in the breast cancer context 41,45 and 1 using mixed-methods in the prostate cancer context 33 ). The other used a novel study design featuring standardized patients to evaluate communication behaviors among 86 providers and found that in only 21% and 3% of encounters did providers express opinions suggesting that patients at high maternal or paternal breast cancer risk, respectively, were candidates for genetic testing.…”
Section: Communication-related Behaviors Regarding Genetic Tests For mentioning
confidence: 99%
“…The other used a novel study design featuring standardized patients to evaluate communication behaviors among 86 providers and found that in only 21% and 3% of encounters did providers express opinions suggesting that patients at high maternal or paternal breast cancer risk, respectively, were candidates for genetic testing. 34 Two additional studies used cross-sectional surveys to assess the extent to which PCPs adhered to clinical guidelines in discussions about consenting to hereditary breast and ovarian cancer testing 39,54 and observed that many were non-adherent (e.g., among 81 providers, 39% did not always discuss implications for family, and 64% did not always discuss the possibility of another hereditary cancer syndrome 54 ). Furthermore, two studies reported limited instances of discussions between PCPs and patients regarding direct-to-consumer testing (e.g., with 71% 45 to 92% 33 of providers not having had a patient ask questions about direct-to-consumer testing).…”
Section: Communication-related Behaviors Regarding Genetic Tests For mentioning
confidence: 99%